Tangential Biopsy Thickness versus Lesion Depth in Longitudinal Melanonychia: A Pilot Study - Nilton Di Chiacchio; Walter Refkalefsky Loureiro; Nilceo Schwery Michalany; Felipe Veiga Kezam Gabriel (Dermatology Research and Practice)
Longitudinal melanonychia can be caused by melanocyte activation (hypermelanosis) or proliferation (lentigo, nevus or melanoma). Histopathologic examination is mandatory for suspicious cases of melanomas. Tangential biopsy of the matrix is an elegant technique avoiding nail plate dystrophy, but it was unknown whether the depth of the sample obtained by this method is adequate for histopathologic diagnosis. Twenty-two patients with longitudinal melanonychia striata were submitted to tangential matrix biopsies described by Haneke. The tissue was stained with hematoxylin-eosin and the specimens were measured at 3 distinct points according to the total thickness: largest (A), intermediate (B) and narrowest (C) then divided into 4 groups according to the histopathologic diagnosis (G1: hypermelanosis; G2: lentigos; G3: nevus; G4: melanoma). The lesions were measured using the same method. The mean specimen/lesion thickness measure values for each group was: G1: 0,59/0,10 mm, G2: 0,67/0,08 mm, G3: 0,52/0,05 mm, G4: 0,58/0,10 mm. The general average thickness for all the specimens/lesions was 0,59/0,08 mm. We concluded that the tangential excision, for longitudinal melanonychia, provides an adequate material for histopathological diagnosis.